Key factors influencing the adoption of co-living spaces by generation Z in Ipoh, Perak / Nurul Afiqa Farhani Mohd Sufian - Mohd Sufian, Nurul Afiqa Farhani (Universiti Teknologi MARA (UiTM), 2025)
In light of growing housing cost and urbanization, this study explores the major variables driving Generation Z’s adoption of co-living spaces in Ipoh, Perak. The research study had used quantitative method to collect the data. Then, the data were collected by using questionnaire form that had been distributed among the Generation Z in Ipoh, Perak. Analysis method that was used in analyzing the data was descriptive analysis. The data were analyzed by using descriptive analysis.